Busy Boards, Firm Performance and Operating Risk - Kin-Wai Lee,; Char-Lee Lok, (Asian Academy of Management Journal of Accounting and Finance, 2020)
Using a sample of listed firms in Malaysia, Philippines, Singapore and Thailand, this paper examines the association between busy board of directors and firm performance. We offer three results. First, we find that firm performance (measured by operating profitability and market-to-book equity) is negatively associated with busy boards. Second, we find that firms with busy boards have higher operating risk (measured by volatility of return on assets, volatility of stock returns and volatility of operating cash flow). Third, we find that the association between firm performance and busy boards is conditional on the firm’s life cycle stage. For firms in the growth stage, busy boards are beneficial to firm performance suggesting that the experience knowledge and reputation accumulated with multiple directorships help busy directors to more effectively advise these firms. In contrast, for firms in the maturity stage of their life cycle, busy boards are detrimental to firm performance suggesting the monitoring role of board is weakened by multiple directorships.